Stereodiscus pseudotrivialis (Russulales, Basidiomycota), a new species from the Patagonian Andes of Argentina - Gorjón, S.p.; Greslebin, A.g. (Phytotaxa, 2024)
The aim of this work is to contribute to the knowledge of the diversity of stereoid fungi growing in the Patagonian Andes. In a recent survey we have found a species of Stereodiscus growing on Nothofagus antarctica in Southern Argentina, closely related to Stereodiscus trivialis but with distinct smaller basidiospores and characteristically encrusted pseudocystidia. The new species is described based on morphological features and phylogenetic ITS and 28S nuc-LSU data. In addition, a key to the known species of Stereodiscus is provided.